Prospecção geofísica de água subterrânea por eletroresistividade - Vila do Caju-Una e Vila do Céu - Soure – Marajó - Pará - RIBEIRO, David Silva (2020)
Fishing communities ' Vila Céu ' and ' Vila Caju -Una ' villages are the seat of the Municipality of Soure , in Marajo , Pará , where nearly a hundred families reside . Although the villages are located near the town of Soure , are not assisted with regular public water supply . There is only one community well dug in dune with small supply of brackish water , heavy dependence on rainfall, drying up in the dry season , has color because of the iron and organic matter. Furthermore, there is a great risk of contamination of the pits , since the entire area of towns and sandy dunes on swamp land . Another problem in terms of contamination is the existence of a cemetery in the area of residences . The city of Soure supplies the Villages , by water truck , only twice a week.These facts cited above gave reason for this geophysical study for determination of aquifer planning to contribute to the management of public water supply in these communities . 3 vertical electrical soundings , whose result investigates more than 50 meters from the subsurface but showed very low resistivity values corresponding to the presence of layers of clays and some mangroves and high values of resistivity corresponding to the presence of dunes in superficial layers were used.With these negative results hydrogeological the villages, the survey was extended to the village and town of SoureGatestone where aquifers that can serve as a solution for supply to villages through pipelines were identified.